Simulation of stress-assisted localised corrosion using a cellular automaton finite element approach. (June 2018) - Fatoba, O.O.; Leiva-Garcia, R.; Lishchuk, S.V.; Larrosa, N.O.; Akid, R.
Highlights: Stress-assisted localised corrosion is simulated using cellular automata finite element approach. Localised corrosion component of the damage is modelled using cellular automata. Stress concentration effect of pit geometry is analysed using finite element method. A feedback loop between both models allows simulation of stress-assisted localised corrosion. Comparison of simulation results with experimental measurements show good agreement. Abstract: In this paper, the overall corrosion damage process is modelled sequentially using cellular automata (CA) to describe the localised corrosion component, and finite element analysis (FEA) to account for the mechanical component resulting from the stress concentration effect of the corrosion defect (pit). Synchronous execution of the CA and FEA, and provision of feedback between both provides a good approximation of stress-assisted pit development. Qualitative and quantitative comparison of simulation results with experimental measurements show good agreement. In particular, the model shows that mechanical effects, notably plastic strain, accelerates the rate of development of localised corrosion.